PERUBAHAN POLA PIKIR, LINGKUNGAN, LUAS LAHAN TERHADAP MOTIVASI GENERASI MUDA MELALUI MINAT PETANI SEKTOR PANGAN DI KABUPATEN DELI SERDANG - Putra, Angga Dwi Kelana; Noer, Zulheri; Sibuea, Mhd Buhari; Sibuea, Faiz Ahmad (AGRIBIOS, 2025)
Food is a crucial sector in meeting the food needs of society. Food is the forerunner of the economic growth sector, with the main driver being farmers. Farmers are no longer young, but in this case the agricultural sector is no longer a concern for the younger generation to work in the agricultural sector. With the decline in the number of people working in the agricultural sector, the younger generation is starting to move away from agriculture. The desire of the younger generation to work in the agricultural sector has diminished, they tend to choose jobs in the non-agricultural sector. The purpose of this study is to determine the attitude, environment, land area on the motivation of the younger generation through the interest of food sector farmers in Deli Serdang Regency. This research method uses a quantitative approach reinforced with descriptive qualitative data using questionnaires with structural equation modelling data analysis with a sample size of 65 farmers. The results showed that the mindset, environment on the motivation of the younger generation through the interest of farmers produced a significant positive effect. While the land area on the motivation of the younger generation and interest produces a positive but insignificant effect. The R-squared results were Y-motivation 84.0% and Z-interest 78.2%.